DESAIN RUTE JALAN DAN AREA PIT PADA PENAMBANGAN BATUBARA TERBUKA - , AZIZUL IZZA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Road (route) is the vital facility in coal mining activity. Road is the most important thing as the media of the transportation for carrying the coal deposit from the excavation site to the stock pile, disposal area, or to the access of hauling area to the harbor. The route which is so vital needs a good design according to the specification in order to obtain the efficient and effective mobilization. The design parameters need attention such as the passing through transportation tools with biggest specification, the plan of velocity along the route, horizontal curve and vertical curve, the slope of the street, the corridor wide of the street. The software technology has been developed for route designing and pit area designing. One of the software which is most used in route designing is surpac. Surpac can do route design and pit design in excavation like horizontal curve design and vertical curve design, super elevation, volume calculation, and bench design. The data required is topographic contour data, situation data, and block boundary in .str formatted. The steps in designing process are DTM making, the pit design, the design of the excavation transportation routes, the merging of pit design with excavation transportation route, and cut and fill volume calculation. Pit design is the most complex step because there are some parameters like the bench slope, the bench high, the berm wide, and ramp wide. Route design needs some combined designs formed vertical curve design which is connected to the topography elevation, horizontal curve, and super elevation design for avoiding so the vehicle is still on its way. The result from the route design, obtained the long of the route connecting the main street to the excavation area in Payabenawa block is 1,692.658 meters meanwhile in Togan block is about 1,969.19 meters. The fill volume can be obtained from the result of the calculation of cut and fill is about 54,991.881 m3 and the cut volume is about 98,282.437 m3 with the corridor wide is 35 meters. The large of the pit area in Togan block obtained from the result of the pit design is 47.0636108 ha and Payabenawa block is 24.84128 ha meanwhile the volume of cutting in pit design for Togan block is 14,598,599.72 m3 and Payabenawa block is 6,602,586.50 m3.